The effects of electronic cigarette emissions on systemic cotinine levels, weight and postnatal lung growth in neonatal mice. - Sharon A McGrath-Morrow; Madoka Hayashi; Angela Aherrera; Armando Lopez; Alla Malinina; Joseph M Collaco; Enid Neptune; Jonathan D Klein; Jonathan P Winickoff; Patrick Breysse; Philip Lazarus; Gang Chen (PLoS ONE)
Background/objective Electronic cigarette (E-cigarettes) emissions present a potentially new hazard to neonates through inhalation, dermal and oral contact. Exposure to nicotine containing E-cigarettes may cause significant systemic absorption in neonates due to the potential for multi-route exposure. Systemic absorption of nicotine and constituents of E-cigarette emissions may adversely impact weight and lung development in the neonate. To address these questions we exposed neonatal mice to E-cigarette emissions and measured systemic cotinine levels and alveolar lung growth. Methods/main results Neonatal mice were exposed to E-cigarettes for the first 10 days of life. E-cigarette cartridges contained either 1.8% nicotine in propylene glycol (PG) or PG vehicle alone. Daily weights, plasma and urine cotinine levels and lung growth using the alveolar mean linear intercept (MLI) method were measured at 10 days of life and compared to room air controls. Mice exposed to 1.8% nicotine/PG had a 13.3% decrease in total body weight compared to room air controls. Plasma cotinine levels were found to be elevated in neonatal mice exposed to 1.8% nicotine/PG E-cigarettes (mean 62.34± 3.3 ng/ml). After adjusting for sex and weight, the nicotine exposed mice were found to have modestly impaired lung growth by MLI compared to room air control mice (p<.054 trial 1; p<.006 trial 2). These studies indicate that exposure to E-cigarette emissions during the neonatal period can adversely impact weight gain. In addition exposure to nicotine containing E-cigarettes can cause detectable levels of systemic cotinine, diminished alveolar cell proliferation and a modest impairment in postnatal lung growth.